Law and Ethics in the Business Environment, 9th Edition - Terry Halbert; Elaine Ingulli (Cengage Learning, 2017)
Blend theory with practical applications as LAW AND ETHICS IN THE BUSINESS ENVIRONMENT, 9E presents current controversial issues at the intersection of business, law, and ethics. Using an engaging, student-friendly in tone, this edition encourages lively classroom debate on pertinent topics, from climate change to the gig economy to telematic surveillance to transgender workplace rights. The organization and support within this edition make is easy to present topics and encourage insightful thinking. Specific prompts and meaningful assignments engage students and create an interactive classroom environment. The authors complete each case and reading with questions that guide students in applying their knowledge in new scenarios as they sharpen critical thinking skills. Projects at the end of each chapter vary from role play and mock trials to negotiation exercises.